بناء مقياس قلق الموت الناجم عن فيروس كورونا (كوفيد 19) لدى المجتمع الجزائري - بن موسى, عبد الوهاب; بوفرة, مختار (جامعة الوادي - University of Eloued, 2023)
تهدف الدراسة الحالية إلى بناء مقياس قلق الموت الناجم عن فيروس كورونا والتأكد من خصائصه السيكومترية، ولتحقيق هذا الهدف تم بناء المقياس ليكون في صورته النهائية متكونا من 17بندا وتم تطبيقه على عينة مكونة من 202 فردا، وللتحقق من خصائصه السيكومترية تم حساب الصدق بالإعتماد على ثلاث طرق: الصدق الظاهري والإتساق الداخلي، والصدق التمييزي، وتم التحقق من الثبات بطريقتين، معامل ألفا كرونباخ والتجزئة النصفية، وتوصلت النتائج إلى أن الإتساق الداخلي تراوحت قيمته بين 0,175-0,667، أما قيمة معامل الثبات باستخدام التجزئة النصفية بعد التصحيح بلغت ,7610، بينما بلغ معامل ألفاكرونباخ ,8140، أي أن المقياس يتمتع بدلالات مقبولة وجيدة من صدق وثبات ما يجعلنا نقول أنه يتمتع بخصائص سيكومترية جيدة، ومنه يمكن إستخدامه لقياس قلق الموت الناجم عن فيروس كورونا.The current study aims to build a scale of death anxiety caused by the Corona virus (Covid 19) and to ascertain its psychometric properties. Validity was calculated based on three methods: apparent honesty, internal consistency, and discriminative honesty. The reliability was verified by two methods:Cronbach's alpha coefficient and half-segmentation. The results concluded that the internal consistency ranged between 0.175-0.667, and the value of the reliability coefficient was by using the half-segmentation after correction 0,761while Cronbach's alpha coefficient reached 0,814 meaning that the scale has acceptable and good indications of sincerity and stability, which makes us say that it has good psychometric properties, and from it it can be used to measure death anxiety caused by the Corona virus (Covid 19).
Building a criterion of death anxiety due to Covid 19 In Algerian society
مقال
Keywords: مقياس قلق الموت ، الخصائص السيكومترية ، الصدق، الثبات ، فيروس ، كورونا; death anxiety scale, psychometric properties,Corona Virus.